2014
DOI: 10.1007/s10021-014-9792-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Nitrogen-Saturation in a Seasonally Dry Chaparral Watershed: Limitations of Traditional Indicators of N-Saturation

Abstract: To evaluate nitrogen (N) saturation in xeric environments, we measured hydrologic N losses, soil N pools, and microbial processes, and developed an N-budget for a chaparral catchment (Sierra Nevada, California) exposed to atmospheric N inputs of approximately 8.5 kg N ha -1 y -1. Dual-isotopic techniques were used to trace the sources and processes controlling nitrate (NO 3 -) losses. The majority of N inputs occurred as ammonium. At the onset of the wet season (November to April), we observed elevated streamw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 93 publications
2
64
0
Order By: Relevance
“…WEON decreased in step with irrigation frequency producing smaller NO pulses upon rewetting dry soils at the onset of the wet season. In support of NH 4 + oxidation, we observed high NO 3 − concentrations and nitrification rates upon rewetting soils-a pattern observed in our study site and other drylands (26,32)-and note that a 31‰ δ-15 N fractionation effect is consistent with nitrification (32, 45). Although we cannot conclusively differentiate between nitrification or nitrifier denitrification as the source of NO, nitrifier denitrification can account for a substantial fraction of NO emissions (11,46) and may best explain the [*δ- 18 O]NO isotopic trends we observed.…”
Section: N]nosupporting
confidence: 60%
See 4 more Smart Citations
“…WEON decreased in step with irrigation frequency producing smaller NO pulses upon rewetting dry soils at the onset of the wet season. In support of NH 4 + oxidation, we observed high NO 3 − concentrations and nitrification rates upon rewetting soils-a pattern observed in our study site and other drylands (26,32)-and note that a 31‰ δ-15 N fractionation effect is consistent with nitrification (32, 45). Although we cannot conclusively differentiate between nitrification or nitrifier denitrification as the source of NO, nitrifier denitrification can account for a substantial fraction of NO emissions (11,46) and may best explain the [*δ- 18 O]NO isotopic trends we observed.…”
Section: N]nosupporting
confidence: 60%
“…Based on these effects, we expected plant phenology would help explain seasonal NO emission patterns at our site [i.e., explain why NO emissions increased as soils dried and plants senesced, similar to observations in another dryland study (18)]. In support of plants controlling NO emissions, differences in plant species composition explained differences in NO flux between two forested sites (33), whereas other studies have suggested that plant N uptake controls hydrologic N loss (26,34) and, therefore, plants should also be capable of influencing gaseous N export (2,18,26). Thus, during the dry season, NO emissions likely increased because the shutdown in plant N uptake increased N supply to NOproducing processes and reactions.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations